Factors influencing the effect of locking plate fixation in proximal humeral fractures of the elderly - Zhao, Kangquan; Pi, Bin; Wang, Yimeng; Wan, Guoyang; Shen, Ji; Yang, Huilin (International Surgery Journal, 2016)
Background:Curative effect following the locking plate fixation of proximal humeral fractures in the elderly have been inconsistent, factor that contributes to the outcomes remains unknown. This study aims to analyse the factors influencing the curative effect of locking plate fixation in proximal humeral fractures of the elderly. Methods: A retrospective analysis was conducted for 72 elderly patients of proximal humeral fractures who had been treated from January 2010 to August 2013. Among the patients, 26 were male and 46 were female. The patients’ age ranged from 60 years old to 78 years old, with an average age of 70.2 years. Constant score was used as clinical outcome measure. Gender, fracture type, plate position, varus of the head-shaft angle, associated injury, and the time to begin functional training after operation were identified as prognostic factors. Results:The patients were followed up for 18 months to 48 months with a mean period of 30.4 months. The constant score ranged from 33 to 91, with an average of 79.1. Shoulder joint function had a significant correlation with fracture type, plate position, and varus of the head-shaft angle. No significant difference was found between shoulder joint function and gender, associated injury, and the time to begin functional training after operation. Conclusions:Fracture type, plate position, and varus of the head-shaft angle were key factors affecting the shoulder function after operation.